Hydration Deficit in 9- to 11-Year-Old Egyptian Children. (6th October 2015) - Gouda, Zaghloul; Zarea, Mohamed; El-Hennawy, Usama; Viltard, Mélanie; Lepicard, Eve; Hawili, Nasrine; Constant, Florence
Background . Children who drink too little to meet their daily water requirements are likely to become dehydrated, and even mild dehydration can negatively affect health. This is even more important in Middle-Eastern countries where high temperatures increase the risk of dehydration. We assessed morning hydration status in a sample of 519 Egyptian schoolchildren (9-11 years old). Methods . Children completed a questionnaire on breakfast intakes and collected a urine sample after breakfast. Breakfast food and fluid nutritional composition was analyzed and urine osmolality was measured using osmometry. Results . The mean urine osmolality of children was 814 mOsmol/kg: >800 mOsmol/kg (57%) and >1000 mOsmol/kg (24.7%). Furthermore, the results showed that a total water intake of less than 400 mL was associated with a significant higher risk of dehydration. Surprisingly, 63% of the children skipped breakfast. Conclusions . The results showed that a majority of Egyptian schoolchildren arrive at school with a hydration deficit. These results highlight the fact that there is a need to educate schoolchildren about the importance of having a breakfast and adequate hydration.